Hieracium richianum (Asteraceae), a new species of H. sect. Alpina from the Eastern Carpathians in Romania - Szeląg, Zbigniew (Phytotaxa, 2020)
Hieracium richianum, a new, apomictic, tetraploid (x = 9) species is described from the Ciucaș Mountains, Eastern Carpathians, Romania. It belongs to the H. fritzei aggregate comprising taxa of presumably hybrid origin between H. alpinum and H. prenanthoides. The new species is illustrated with photos of the holotype and living plants.